The analysis of the possibilities of using a virtual reality system in fitness training - Nitkiewicz, Szymon; Zaremba, Arnold; Tytuła, Jakub (Technical Sciences, 2023)
Virtual Reality (VR) is an amazing tool in the field of interaction, simulation, and entertainment between humans and computers. This technology is often used for recreational purposes in combination with physical activities. The main objective of this study was to compare intermittent training with continuous training on the shooting range. The first part of the article presents the essence of virtual reality and the possibilities that arise from its use. Then the created virtual environment, in which the shooter is located, and the way the study has been carried out are presented. The attempts of the participants were shown and evaluated. The realistic physics of movement and environment interactions have been designed into this map. The main aspects of the modelled and programmed shooting range were presented and their use has been described. The following section describes the research process and the analysis of the results of the test carried out on eight participants who had not previously been exposed to virtual reality. The test subjects were divided into two groups, one intermittent training and the other continuous training. The results of these groups were compared to assess which forms of training in a virtual reality environment were more beneficial.